An Improvement of the Efficiency of Dye Sensitized Solar Cells by TiO2 Blocking Layer - โพธิพิทักษ์ ดร.ชานุ; ขุนจารย์ สุกัลยา (Journal of Food Health and Bioenvironmental Science, 2019)
This research aims to improve the efficiency of dye-sensitized solar cell (DSSC) with the synthesis of TiO2 sol gel which is modified from surfactant-assisted sol gel techniques to prepare the TiO2 blocking layer by Dip and Spin coating methods. TiO2 blocking layer film characterization was analyzed by SEM, XRD and UV-vis spectroscopy techniques. The performance and internal resistance of the DSSC were studied by I V Tester and Electrochemical impedance spectroscopy, respectively. The recombination process was measured by using a transient voltage graph. The results showed that coating of TiO2 blocking layer film by Dip coating, which has 280 nm of thickness, had a maximum efficiency at 3.75% (14.33% increase) when compared to a standard cell at 3.28%. The TiO2 blocking layer reduces the recombination reaction at the FTO/electrolyte interface.